# Solve using the Square Root Property (x-15)^2=49 (x-15)2=49
Take the square root of each side of the equation to set up the solution for x
(x-15)2⋅12=±49
Remove the perfect root factor x-15 under the radical to solve for x.
x-15=±49
Simplify the right side of the equation.
Rewrite 49 as 72.
x-15=±72
Pull terms out from under the radical, assuming positive real numbers.
x-15=±7
x-15=±7
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
x-15=7
Move all terms not containing x to the right side of the equation.
Add 15 to both sides of the equation.
x=7+15
x=22
x=22
Next, use the negative value of the ± to find the second solution.
x-15=-7
Move all terms not containing x to the right side of the equation.
Add 15 to both sides of the equation.
x=-7+15
x=8
x=8
The complete solution is the result of both the positive and negative portions of the solution.
x=22,8
x=22,8
Solve using the Square Root Property (x-15)^2=49     